2020
DOI: 10.1080/21645515.2020.1737457
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a quality improvement continuing medical education intervention on physicians’ vaccination practice: a controlled study

Abstract: This study investigated the impact of a longitudinal quality improvement continuing medical education (CME) intervention on influenza and pneumococcal vaccination rates for patient populations at high-risk or aged ≥ 65. An observational cohort design with a propensity score to adjust for vaccine eligibility between the intervention and control cohorts was utilized to assess the impact of the intervention among primary care physicians. The intervention was a three-stage quality improvement initiative with CME l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…We administered an online survey to 400 United States HCPs to assess knowledge, attitudes, and practices regarding adult HepA/ 81.0% 11 and receiving training to stay updated on guidelines was a significant predictor of familiarity with the ACIP in the current study. HCPs who reported that it was important to vaccinate at-risk patient populations according to the guidelines or that they were very likely to recommend vaccines to at-risk patients were more likely to self-report adherence to the guidelines than other HCPs.…”
Section: Discussionmentioning
confidence: 96%
“…We administered an online survey to 400 United States HCPs to assess knowledge, attitudes, and practices regarding adult HepA/ 81.0% 11 and receiving training to stay updated on guidelines was a significant predictor of familiarity with the ACIP in the current study. HCPs who reported that it was important to vaccinate at-risk patient populations according to the guidelines or that they were very likely to recommend vaccines to at-risk patients were more likely to self-report adherence to the guidelines than other HCPs.…”
Section: Discussionmentioning
confidence: 96%
“…Conjointly, the literature provided evidence for effectiveness of prompt point of care in improving the vaccine counseling rate by physicians [ 20 ]. Moreover, the available evidence proves the positive impact of physicians’ knowledge [ 21 ] and performance feedback on the compliance of physicians with guidelines [ 22 ]. The current study found that several changes in process changes and continuous learning improve the compliance rate.…”
Section: Discussionmentioning
confidence: 99%
“…The initiative incorporated 3 major components: (1) clinician and team education, (2) pre-visit counseling by registered nurses, and (3) interdisciplinary pre-visit huddles. Although quality improvement efforts have utilized elements of pre-visit planning, point-of-care reminders, and educational training, 7 - 9 none have applied a combined effort like the one implemented in this initiative.…”
Section: Discussionmentioning
confidence: 99%
“…There have been multiple quality improvement studies that have assessed innovative strategies to improve pneumococcal vaccine rates. 7 - 9 Desai et al 7 implemented point-of-care reminders, Sivaraman et al 8 initiated pre-visit planning, and a study completed by Kawczak et al 9 showed that having physician involvement and continued medical education training were beneficial to improving pneumococcal vaccination rates. None of these studies though utilized all the elements implemented in our novel approach.…”
Section: Introductionmentioning
confidence: 99%